Enhancing Pedagogy in Islamic Studies Methodology: A Focus on Hadith Instruction - Umam, Hoerul; Khadijah, Ifah (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
This study endeavors to investigate strategies for enhancing the pedagogy of Islamic Studies methodology, rendering it more efficacious and pertinent to contemporary requisites, with particular emphasis on advancing the effectiveness of instruction and the progression of hadith studies within the domain of Islamic higher education. The overarching objective is to establish a comprehensive framework governing the methodological approach to the instruction of hadith. The methodological framework adopted in this investigation is inherently descriptive and analytical in nature. Data acquisition was undertaken through the meticulous analysis of scholarly literature, encompassing documentary research, and direct observation of hadith instruction within the precincts of Islamic higher education institutions. A scrupulous evaluation of the construct of Islamic Studies Methodology in the context of hadith pedagogy has unearthed a plethora of inadequacies that necessitate immediate rectification. This study posits a compelling argument for the imperative of reform in the domain of hadith instruction within Islamic higher education. The required initiatives for the amelioration of hadith instruction encompass: (1) A concerted amplification of the focus on the scholarly study of hadith methodology, with a view to fostering an enduring culture of erudition; (2) Augmentation of accessibility to digital resources and traditional Islamic literature; (3) The empowerment of innovation and technology as pedagogical tools to engender a more immersive and captivating learning experience; (4) Advocacy for an interdisciplinary approach to hadith instruction, affording students the opportunity to scrutinize hadith from a multiplicity of disciplinary vantage points; (5) The facilitation of an environment that encourages open discourse and a profound comprehension of the contextual underpinnings of hadith; and (6) The inculcation of the imperative of integrating both normative and historical dimensions in the teaching of hadith, to ensure a more contextualized understanding. These initiatives are anticipated to contribute to the augmentation of the efficacy of hadith instruction within Islamic higher education, providing students with a deeper comprehension of the subject matter and preserving the relevance of hadith in the contemporary milieu.